Development of a low-cost laser range-finder - Kaldén, Peter; Sternå, Erik (My University, 2015)
This is a development report that covers the work attempting to design and construct a laser based LIDAR. The goal of the project was to design a cheap laser rangefinder capable of performing scanning measurements. This was intended to be an open-source sensor primarily aimed at engineers lacking a cost viable sensor for positioning. The target specifications of the system were to have a measurement range from 0.5 m to 5 m with a measurement accuracy of 0.05 m. Scanning was initially specified however it was removed due to time constraints, however the requirements to be able to handle scanning measurements was retained to enable it scanning to be realized at a later time. Scanning with a 360 degrees field of view with a 1 degree angular resolution was specified, making a measurement rate of atleast 3.6 kHz a requirement. The total cost limit set was e120. The major part of this thesis discusses the selection of suitable components and the reasoning behind their choice. The focus when choosing components was primarily to minimize component costs and adhere to international safety regulations while still fulfilling the specifications. Since the goal was to make this project open source the reasoning and process of development is vital for anyone wishing to continue the development. The selected components were assembled and tested. The approximated total cost of the components for the system ended at e(125), slightly higher than the cost limit without any manufacturing cost included. It is however close to the limit and it might be possible to reduce the cost with alternative components. The control system, the time measurement, the transmitter and the optics were all verified working and fulfilling their part of the specifications. However the detector and amplifier were unable to receive and amplify the very weak return signal preventing the system from being verified in its entirety.
Keywords: Innovation och entreprenörskap (nyttiggörande); Elektronisk mät- och apparatteknik; Inbäddad systemteknik; Övrig elektroteknik, elektronik och fotonik; Innovation & Entrepreneurship; Electronic measurement and instrumentation; Embedded Systems; Other electrical engineering, electronics and photonics